Peran Perpustakaan Dalam Meningkatkan Minat baca Siswa di MAN 1 Ngawi - Muhammad Alvian Nur Risqi; Amanda Nuria Rahmawati; Yunita Yunita (Universitas PGRI Madiun, 2026)
School libraries play a significant role in supporting the learning process and fostering students' reading interest. This study aims to determine the role of the library in enhancing students' reading interest at MAN 1 Ngawi. The research employed a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis involved data reduction, data display, and conclusion drawing. The results of the study indicate that the library plays a vital role in increasing students' reading interest by providing book collections, lending services, literacy programs, and facilities that support learning activities. Although there are still some challenges, the various efforts undertaken by the library have had a positive impact on increasing student visits and reading habits. Thus, the library holds an essential role in supporting a literacy culture within the school environment.